INDUSTRY 4.0 AND THE NEED FOR PROPER GOVERNANCE - Syarif Hidayat (Journal of Social Political Sciences, 2020)
This paper attempts to fill the gap of that literature by fosussing more on the issu of what is the most industry 4.0 challenge for governing a nation state?. In so doing, the paper will begin with outlining briefly the origin and componets of Industry 4.0, as well as its challenge for the governance. After that, the discussion will be directed to criticise the current Good Governance concept, then proceeded to propose the so called a Proper Governance concept which is belief more suitable to meet the challenge of industry 4.0.